2015
DOI: 10.1007/s10461-015-1097-8
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Acceptability on HIV Self-testing Among Key Populations: A Literature Review

Abstract: HIV self-testing (HIVST) is a potential strategy to overcome disparities in access to and uptake of HIV testing, particularly among key populations (KP). A literature review was conducted on the acceptability, values and preferences among KP. Data was analyzed by country income World Bank classification, type of specimen collection, level of support offered and other qualitative aspects. Most studies identified were from high-income countries and among men who have sex with men (MSM) who found HIVST to be acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

48
408
3
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(465 citation statements)
references
References 34 publications
48
408
3
6
Order By: Relevance
“…This striking result is consistent with findings from a pilot study we previously conducted in the study region, in which male partner testing was reported to have occurred for 91% of women seeking ANC and 86% of women receiving PNC . The study results are also consistent with the high acceptability of self-testing that has been documented in SSA and elsewhere (Choko et al 2011;Napierala Mavedzenge et al 2013;Figueroa et al 2015).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This striking result is consistent with findings from a pilot study we previously conducted in the study region, in which male partner testing was reported to have occurred for 91% of women seeking ANC and 86% of women receiving PNC . The study results are also consistent with the high acceptability of self-testing that has been documented in SSA and elsewhere (Choko et al 2011;Napierala Mavedzenge et al 2013;Figueroa et al 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Overall, the high levels of partner testing achieved in the HIVST group are consistent with results from various studies that have shown extremely high acceptability of HIVST in SSA (Choko et al 2015;Napierala Mavedzenge et al 2013;Figueroa et al 2015;Johnson et al 2014).…”
Section: Discussionsupporting
confidence: 84%
“…Confidentiality, convenience, immediacy and the opportunity to increase testing frequency are commonly cited benefits of HIVST (22)(23)(24)(25)(29)(30)(31)(32). Barriers tend to be concerns around dislocation from care pathways, the possibility of coercive testing practices, and perceived issues with selfefficacy as well as kit accuracy (31,33,34).…”
Section: Understanding Implementation Contexts: Values and Preferencesmentioning
confidence: 99%
“…Her yıl dünya genelinde 2 milyondan fazla yeni HIV enfeksiyon olgusu meydana gelmekte ve tüm yeni yetişkin HIV enfeksiyonları-nın tahminen %40'ını bu gruplar oluşturmaktadır (8) . Eşcinsel erkekler arasında HIV salgınının, 1990'ların ortalarında yeniden ortaya çıkması, Batı Avrupa, Kuzey Amerika, Avustralya ve Çin gibi dünyanın pek çok yerinde önemli bir halk sağlığı sorunu yaratmıştır.…”
Section: Introductionunclassified
“…Yine Amerika Birleşik Devletleri'nde, damar içi uyuşturucu kullananların ise %49'unun son 12 ay içinde bir HIV testi yaptırdığı tahmin edilmektedir (11) . Birleşmiş Milletler HIV/AIDS Ortak Programı (UNAIDS)'ın ''90 90 90'' hedeflerine ulaşılması (%90'lık kesimin durumundan haberdar olması, %90'ının antiretroviral tedaviyi (ART) alması ve %90'ınında virus supresyonu uygulanması) bu riskli popülasyonların HIV test ve tedavilerine ulaşması konusunda çaba göstermeden olası olmayacaktır (8) .…”
Section: Introductionunclassified